Comparative analysis of KRAS codon 12, 13, 18, 61, and 117 mutations using human MCF10A isogenic cell lines - Stolze, Britta (Sci Rep, 2015)
KRAS mutations occur in one third of human cancers and cluster in several hotspots, with codons 12 and 13 being most commonly affected. It has been suggested that the position and type of amino acid exchange influence the transforming capacity of mutant KRAS proteins. We used MCF10A human mammary epithelial cells to establish isogenic cell lines that express different cancer-associated KRAS mutations (G12C, G12D, G12V, G13C, G13D, A18D, Q61H, K117N) at physiological or elevated levels, and investigated the biochemical and functional consequences of the different variants. The overall effects of low-expressing mutants were moderate compared to overexpressed variants, but allowed delineation of biological functions that were related to specific alleles rather than KRAS expression level. None of the mutations induced morphological changes, migratory abilities, or increased phosphorylation of ERK, PDK1, and AKT. KRAS-G12D, G12V, G13D, and K117N mediated EGF-independent proliferation, whereas anchorage-independent growth was primarily induced by K117N and Q61H. Both codon 13 mutations were associated with increased EGFR expression. Finally, global gene expression analysis of MCF10A-G13D versus MCF10A-G12D revealed distinct transcriptional changes. Together, we describe a useful resource for investigating the function of multiple KRAS mutations and provide insights into the differential effects of these variants in MCF10A cells.